Prevention and risk factors associated with incidence of central line associated bloodstream infection: a narrative review - V., Sivakumar; Shazneen, Fathima; Rijo S., Jefrin; Shiny, Jenita (International Journal of Research in Medical Sciences, 2024)
Central line-associated bloodstream infections (CLABSI) are a critical concern in healthcare settings, associated with high mortality rates and substantial financial burdens. This article highlights the various risk factors contributing to CLABSI, emphasizing both intrinsic and extrinsic factors, such as patient age, gender, underlying medical conditions, and catheterization duration. The prevention of CLABSI is addressed through a comprehensive bundle of evidence-based interventions, including hand hygiene, proper catheter insertion, skin preparation, catheter kits, selection of catheters, and maintenance bundles. Antimicrobial lock and flush solutions are crucial in eradicating microbes within catheter lumens. Furthermore, chlorhexidine bathing is recommended to reduce skin contaminants. Implementing these strategies collectively can significantly reduce the incidence of CLABSI, enhancing patient safety and reducing healthcare expenditure.